Prevalence of Cardiovascular Diseases (CVDs) in OIC countries: implications on healthcare system - Mazlan, Munirah; Mohamad Diah, Nurazzura; Samsudin, Suhaiza (Universiti Sultan Azlan Shah (USAS), 2018)
Today, cardiovascular diseases (CVDs) are one of the main causes of death around the world, including countries under the banner of the Organization of Islamic Cooperation (OIC). The surge in the prevalence of CVDs is predominantly contributed by demographic changes and adoption of sedentary lifestyles together with deficient in physical activity. The objective of this paper is to examine the patterns of CVDs in OIC countries and how this has significantly affected the healthcare system. Relevant data from 56 OIC countries were obtained from the report by World Health Organization (WHO) in 2016. Descriptive content analysis was conducted to see variations in CVDs across income groups, genders and health conditions. The analysis suggests that CVDs are the main cause of mortality, particularly in high income and upper-middle income countries. Tobacco smoking, alcohol intake, high blood pressure and obesity are the common risk factors which contribute to CVDs. Men are known to have high risk factors compared to women. Indeed, the burden of NCDs has impacted not only on the quality of life of affected individuals and their families, but also on the country’s socio-economic system.